Kondisi Sosial Emosional Anak pada Orang Tua Workaholic di Paud SKB Gudo Jombang - Maharani, Cyntia Aprilistin Putri; Yulianingsih, Wiwin (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
This research aims to describe and analyze the parenting patterns applied by Workaholic parents to early childhood at PAUD SKB Gudo Jombang, as well as the social emotional conditions of children of these Workaholic parents. The research sample consisted of 10 parents who were very busy working. The method used is descriptive qualitative, with data obtained through interviews, observation and documentation studies. The results of the study show that: 1) Workaholic Parenting Patterns: The conceptualization of work addiction still varies, with different views regarding whether Workaholics are seen more as addicts or achievers, and whether work addiction is the result of investing high effort alone or a combination of high effort and a fundamental drive to work hard. 2) Social Emotional Condition of Children: Children of Workaholic parents show good self-awareness, responsibility for themselves, and prosocial behavior